The Implementation of Mindfulness-Based Programs in the Swedish Healthcare System – A Survey Study of Service Providers - Maria Niemi PhD (SAGE Publishing, 2021)
Background The burden of depression and anxiety is on the rise globally. Mindfulness-Based Programs (MBPs) are a particular group of psychosocial programs targeting depression and anxiety. There is growing research and practice interest in MBPs internationally, and they are becoming more commonly implemented in a number of countries’ healthcare services. Objective To systematically map the existing provision of MBPs in the Swedish healthcare sector, in order to understand facilitators and barriers to uptake, and so inform future implementation efforts. Methods We assessed the experiences of MBP implementation among relevant stakeholders in Swedish healthcare settings through an online survey. The survey was designed to gather data on (1) the evidence-base of practice being implemented; (2) the context in which implementation was taking place and (3) the process of facilitation. Respondents were identified through snowball sampling of key stakeholders. Results In total, 129 individuals from 20 of the 21 healthcare regions in Sweden responded to the survey. Our findings showed that there is variation in the types of MBP models being implemented, and that the delivery structure of evidence-based programs were often being modified for implementation. We found some divergence from international guidance on good practice standards for the training of MBP teachers within Swedish implementation processes. The main service context for implementation is primary care; the most important facilitating factors for successful MBP implementation were the presence of a championing individual and support from leadership. The most influential hindering factors for implementation were lack of time, and lack of funding. Conclusion To support integrity and fidelity of MBP implementation in Sweden, a strategic plan and good practice guidelines seem necessary. Also, an evidence-based stepped care model for implementation may work to ensure intervention fidelity in cases where time and funding constraints permit.